(untitled) (Revista de Ciências Agroveterinárias, 2025)
Rice (Oryza sativa L.) is a staple food for more than half of the world’s population, but its production is threatened by salinity, which affects its development in both early and reproductive stages. Gamma radiation-induced mutation has been used to generate genetic variability and develop cultivars better adapted to saline conditions. However, selecting tolerant mutants is challenging due to the genetic complexity of salinity response and the need for large populations. In this study, 100 rice mutants (M5 and M6) and two control cultivars (sensitive and tolerant) were evaluated under salt stress (NaCl 120 mM) in a greenhouse, assessing shoot and root growth and dry weight. Despite the variability generated, no mutant outperformed the tolerant cultivar in all traits analyzed, highlighting the difficulty of selecting promising individuals from small populations. Furthermore, environmental factors may have contributed to inconsistencies between generations, reinforcing the need for large-scale screening. The most effective strategy involves initial field selection, validation under controlled conditions, and further agronomic reassessment. Technologies such as remote sensing-based phenotyping could improve efficiency, but they remain costly. Future studies should integrate new methodologies and keep the selection of salt-tolerant mutants in early generations (M2 and M3) from large populations, alongside yield evaluation to confirm their agronomic applicability under salinity conditions.